Therapeutic exercise attenuates neutrophilic lung injury and skeletal muscle wasting - Files, D. Clark (2015)
Early mobilization of critically ill patients with the acute respiratory distress syndrome (ARDS) has emerged as a therapeutic strategy that improves patient outcomes, such as the duration of mechanical ventilation and muscle strength. Despite the apparent efficacy of early mobility programs, their use in clinical practice is limited outside of specialized centers and clinical trials. To evaluate the mechanisms underlying mobility therapy, we exercised acute lung injury (ALI) mice for 2 days after the instillation of lipopolysaccharides into their lungs. We found that a short duration of moderate intensity exercise in ALI mice attenuated muscle ring finger 1 (MuRF1)–mediated atrophy of the limb and respiratory muscles and improved limb muscle force generation. Exercise also limited the influx of neutrophils into the alveolar space through modulation of a coordinated systemic neutrophil chemokine response. Granulocyte colony-stimulating factor (G-CSF) concentrations were systemically reduced by exercise in ALI mice, and in vivo blockade of the G-CSF receptor recapitulated the lung exercise phenotype in ALI mice. Additionally, plasma G-CSF concentrations in humans with acute respiratory failure (ARF) undergoing early mobility therapy showed greater decrements over time compared to control ARF patients. Together, these data provide a mechanism whereby early mobility therapy attenuates muscle wasting and limits ongoing alveolar neutrophilia through modulation of systemic neutrophil chemokines in lung-injured mice and humans.